Micropore plugging agent for flexible graphite bipolar plate of fuel cell
By using silicone double-header with two (meth)acryloyloxy groups at both ends and microporous plugging agent with high Tg methacrylate monomers, the problem of the plugging agent dissolution when the flexible graphite bipolar plate is exposed to the aqueous ethylene glycol solution at long-term high temperature, achieving high heat resistance and airtightness.
Patent Information
- Application Number
- CN202411881766.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
When existing flexible graphite bipolar plates come into contact with aqueous ethylene glycol solution at long-term high temperatures, partial dissolution of the leak plugging agent leads to pore cracks, gas leakage, and failure.
The silicone double-header with two (meth)acryloyloxy groups at each end and a high Tg methacrylate monomer as the microporous plugging agent are used to form a double-header compound through the esterification and dehydration reaction, combining a leveling agent and a free radical thermal initiator to form a plugging agent with high heat resistance and low curing shrinkage.
The leak plugging agent is insoluble when it comes into contact with the aqueous ethylene glycol solution at long-term high temperatures, maintains airtightness and bending strength, and extends the service life of the flexible graphite bipolar plate.
Smart Images

Figure BDA0005198371180000021 
Figure BDA0005198371180000022 
Figure BDA0005198371180000023
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen fuel cells, and in particular relates to a thermally cured microporous plugging agent for a flexible graphite bipolar plate of a hydrogen fuel cell stack. Background Art
[0002] Fuel cell bipolar plates are the core structural support components of hydrogen fuel cell stacks, and are divided into metal bipolar plates and graphite bipolar plates. Graphite bipolar plates are widely used in commercial vehicle fuel cell stacks because of their easy availability of raw materials, low cost, good chemical corrosion resistance, and long life. However, the flexible graphite plate itself has a microporous structure and must be impregnated with a plugging agent to ensure the airtightness of the bipolar plate. At the same time, after the plugging agent is cured, the flexible graphite plate must be given sufficient mechanical strength, chemical resistance (mainly ethylene glycol resistance) and long-term heat resistance.
[0003] Flexible graphite bipolar plates generally use (meth) acrylate monomers to compound into impregnated resin liquid as plugging agent (refer to Chinese patent CN 107706430B). Free radical thermal initiator is added before use, and the flexible graphite plate is impregnated in the plugging agent, and vacuum or pressure impregnation is performed to allow the plugging agent molecules to penetrate into the micropores of the flexible graphite bipolar plate, and then the plugging agent remaining on the surface of the bipolar plate is cleaned to prevent the plugging agent from affecting the conductivity of graphite after curing on the surface of the bipolar plate. The bipolar plate is then heated and cured in a water bath, and the plugging agent forms a dense network structure after curing, thereby giving the bipolar plate air tightness, compressive strength, chemical resistance and heat resistance.
[0004] After the flexible graphite bipolar plates are assembled into a fuel cell stack, they will be in contact with an ethylene glycol aqueous solution cooling medium at a temperature of 80 to 95°C for a long time during the operation of the fuel cell. They need to have resistance to the long-term high temperature of the ethylene glycol aqueous solution. (Meth)acrylate polymers have a certain solubility in ethylene glycol. As a result, after the fuel cell has been running for a long time, the bipolar plate plugging agent is partially dissolved in ethylene glycol, resulting in holes and cracks, which lead to gas leakage and failure.
[0005] The Tg of the methacrylate polymer or copolymer mentioned in Chinese patent CN 107706430B is relatively low, and there are few components with a Tg exceeding 100°C. The Tg of the long-chain alkyl acrylate polymer is even lower than zero degrees, and it is in a rubbery state at the operating temperature of the fuel cell. The bending strength of the graphite bipolar plate is greatly reduced, and it is difficult to meet the stringent requirements of hydrogen fuel cell vehicles for stable operation under long-term high temperatures. Summary of the invention
[0006] The purpose of the present invention is to provide a micropore plugging agent for flexible graphite bipolar plates of hydrogen fuel cells.
[0007] The technical solution to achieve the purpose of the present invention is:
[0008] In a first aspect, the present invention provides a micropore plugging agent for a flexible graphite bipolar plate, comprising: 30 to 50 parts by weight of an organosilicon double-capping agent having two (meth)acryloyloxy groups at both ends and 50 to 70 parts by weight of a high Tg methacrylate monomer, the total of which is 100 parts by weight, as well as 0.5 to 2 parts by weight of a leveling agent and 0.2 to 1.0 parts by weight of a free radical thermal initiator;
[0009] The organosilicon double-capping agent with two (meth)acryloyloxy groups at both ends has the following structure:
[0010]
[0011] Wherein, R1 represents a methyl group or a hydrogen atom.
[0012] Preferably, the synthesis method of the organosilicon double capping agent having two (meth)acryloyloxy groups at both ends comprises:
[0013] The first step is to use a hydrogen-containing double-capped compound and trimethylolpropane monoallyl ether to carry out a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capped compound containing two hydroxyl groups at both ends.
[0014]
[0015] Step 2: The step of subjecting a double-capped compound having two hydroxyl groups at each end and an excess of (meth) acrylic acid to an esterification dehydration reaction in the presence of an acidic catalyst and a cyclohexane water-carrying agent to generate a double-capped compound having two (meth)acryloyloxy structures at each end:
[0016]
[0017] Wherein, R1 represents a methyl group or a hydrogen atom.
[0018] Specifically, in order to prevent the self-polymerization of acrylic acid during the esterification and dehydration reaction of acrylic acid, a free radical inhibitor needs to be added during the esterification and dehydration reaction, and the amount added is 0.01% to 1% of the total mass of the reactants.
[0019] More specifically, the free radical inhibitor is any one or two or more of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone, and 2,6-di-tert-butyl-4-methylphenol.
[0020] Specifically, the acidic catalyst for the acrylic acid esterification dehydration reaction is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, a strong acidic ion exchange resin and a solid superacid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, a strong acidic ion exchange resin and a solid superacid, and the added amount is 0.1% to 5.0% of the total mass of the reactants.
[0021] Preferably, the high Tg methacrylate monomer is selected from any one of isobornyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuranyl methacrylate, tricyclodecyl (meth)acrylate, dicyclopentadiene (meth)acrylate, (meth)acryloylmorpholine and N,N-dimethylacrylamide, etc. Based on comprehensive considerations such as heat resistance and low viscosity, isobornyl (meth)acrylate, dicyclopentadiene (meth)acrylate or tricyclodecyl methacrylate is preferred.
[0022] Preferably, the leveling agent can be any leveling agent that has a wetting effect on the flexible graphite bipolar plate, and can be determined according to the impregnation amount of the plugging agent after the flexible graphite bipolar plate is wetting. The higher the impregnation amount, the better the effect of the leveling agent. German BYK leveling agents BYK-333 and BYK-3505, and three positive polymer superdispersants such as CH-1, CH-2, CH-3, CH-5, CH-6, CH-7, CH-8, CH-9, etc. are preferred.
[0023] Preferably, the free radical thermal initiator is an initiator with a decomposition temperature of 80 to 95° C., and an azo or peroxide free radical thermal initiator is selected. Free radical thermal initiators such as azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide are preferred.
[0024] Preferably, various antioxidants, anti-aging agents, fluorescent agents, etc. may be added to the above composition based on considerations of weather resistance, heat resistance, and fluorescent recognition.
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] (1) One of the components of the flexible graphite bipolar plate plugging agent of the present invention is an organosilicon double-capping agent with two (meth)acryloyloxy groups at each end. Due to the hydrophobic and oleophobic properties and low surface tension of the organosiloxane structure, it has excellent ethylene glycol resistance and will not swell or dissolve when in contact with ethylene glycol aqueous solution under long-term high temperature. It is particularly suitable for plugging micropores in flexible graphite bipolar plates of hydrogen fuel cells.
[0027] (2) One of the components of the flexible graphite bipolar plate plugging agent of the present invention is a silicone double-capping agent compound with two (meth)acryloyloxy groups at each end, each molecule contains 4 (meth)acryloyloxy groups that can be free radical polymerized, and after copolymerization with a high Tg methacrylate monomer, it has high heat resistance, and at the same time, the curing shrinkage rate is relatively low, and the residual stress is small, which is beneficial for the bipolar plate to maintain good bending strength at high temperature. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to the embodiments.
[0029] (Meth)acrylate monomers have the advantages of low viscosity, strong permeability, and low curing temperature. They are the preferred compounds for micropore plugging agents for fuel cell graphite bipolar plates. Compared with acrylate compounds, methacrylate compounds are more susceptible to free radical thermal curing reactions, and the cured products have higher Tg (glass transition temperature), which means they have higher heat resistance. Therefore, most commercial micropore plugging agents use methacrylate monomers as the main component. However, after the polymerization of methacrylate monomers, few have a Tg exceeding 100°C, and their heat resistance is not as good as that of epoxy resin cured products. Also, because the cross-linking density is not high enough and they contain a large number of polar ester bonds, their resistance to ethylene glycol is not good enough.
[0030] The invention introduces a tetrafunctional monomer containing a methylsiloxane structure, which has high Tg and excellent ethylene glycol resistance.
[0031] The organic silicon double-capping agent with two (meth)acryloyloxy groups at both ends of the invention first uses a hydrogen-containing double-capping agent and trimethylolpropane monoallyl ether to undergo a silylation reaction in the presence of a platinum catalyst to generate a double-capping compound with two hydroxyl groups at both ends, and then the double-capping compound with two hydroxyl groups at both ends and excess (meth)acrylic acid are subjected to an esterification and dehydration reaction in the presence of an acidic catalyst and a cyclohexane water-carrying agent to generate a double-capping compound ATH with two (meth)acryloyloxy structures at both ends.
[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0033] Synthesis of dihydroxy double capping agent:
[0034] Add 100g trimethylolpropane monoallyl ether and 0.01g chloroplatinic acid into a three-necked glass flask with an oil bath and a condenser, stir and heat to 70°C, add 42g hydrogen-containing double-capping agent (1,1,3,3-tetramethyldisiloxane) dropwise, and complete the addition within one hour, then heat to 80°C and continue the reaction for 4h, remove the unreacted hydrogen-containing double-capping agent in vacuo, and obtain a colorless and transparent double-capping agent (double hydroxyl double-capping agent) with two hydroxyl groups at each end. The molecular weight is 482.7.
[0035] Synthesis of bisacryloxy double capping agent (ATH-1 synthesis):
[0036] Add 100g of dihydroxy double-capping agent, 66g of acrylic acid, 6.0g of methylsulfonic acid, 0.06g of MeHQ free radical inhibitor, and 150g of cyclohexane water-carrying agent into a three-necked glass flask with an oil bath and condenser, stir and heat to 85°C for reflux, and regularly release the water brought out with a separatory tube, carefully observe the amount of water retained in the separatory tube until no more excess water is distilled out, and the reaction is considered complete. Cool to room temperature, add excess sodium carbonate to neutralize the residual acrylic acid and acidic catalyst, precipitate and filter, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with two acryloyloxy groups at each end, referred to as ATH-1, with a viscosity of 420mPas and a molecular weight of 698.7.
[0037] Synthesis of bis-methacryloyloxy double-capping agent (ATH-2 synthesis):
[0038] Add 100g of dihydroxy double-capping agent, 79g of methacrylic acid, 1.0g of trifluoromethanesulfonic acid, 0.07g of MeHQ free radical inhibitor, and 180g of cyclohexane water-carrying agent into a three-necked glass flask with an oil bath and condenser, stir and heat to 85°C for reflux, and regularly release the water brought out with a separatory tube, carefully observe the amount of water retained in the separatory tube until no more excess water is distilled out, and the reaction is considered complete. Cool to room temperature, add excess sodium carbonate to neutralize the residual methacrylic acid and acidic catalyst, precipitate and filter, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with two methacryloyloxy groups at each end, referred to as ATH-2, with a viscosity of 487mPas and a molecular weight of 754.7.
[0039] The plugging agent formulations in the embodiments and comparative examples are prepared by mixing the various components and stirring them evenly until the solid substances are dissolved into a transparent liquid.
[0040] The formulations of the embodiments and comparative examples are shown in Table 1 below.
[0041] Table 1
[0042]
[0043] The evaluation method for ethylene glycol resistance is as follows:
[0044] Pour 10g of the plugging agent into a Teflon mold with a diameter of 4.0cm and a height of 2.0cm, heat it in an 80℃ drying oven for 2h, then heat it to 120℃ and continue heating it for 2h to obtain a colorless and transparent cylindrical solid. Put the cylindrical solid into a glass bottle with 50%wt ethylene glycol aqueous solution and seal it, move it into a 90℃ oven and keep it for 1000h, take it out to examine the solubility of the solid and the turbidity of the ethylene glycol aqueous solution, so as to evaluate the ethylene glycol resistance of the plugging agent.
[0045] Ethylene glycol resistance is divided into 4 levels:
[0046] 1. Excellent◎ (the solidified material is intact, the ethylene glycol aqueous solution is transparent and free of foreign matter and turbidity)
[0047] 2. Good ○ (the solidified material has no obvious dissolution, and the ethylene glycol aqueous solution is slightly turbid)
[0048] 3. General △ (the solidified material is obviously dissolved, and the ethylene glycol aqueous solution becomes turbid)
[0049] 4. Very poor × (the solidified material swells and dissolves, and the ethylene glycol aqueous solution is slightly turbid)
[0050] According to Table 1, by comparing Example 1 and Comparative Example 1, it is found that the addition amount of ATH bisacryloxy double capping agent has a crucial influence on the ethylene glycol resistance. ATH bisacryloxy double capping agent addition amount exceeds 30phr (Parts per hundred) to achieve better resistance. When the addition amount of ATH bisacryloxy double capping agent is 10phr, the solidified material is obviously dissolved after aging, and the ethylene glycol aqueous solution becomes turbid. At the same time, the Tg of the obtained solidified material is relatively low, and the heat resistance is also poor.
[0051] The composition of Comparative Example 2 is all high-Tg methacrylate, and the Tg of the cured product is relatively high. However, because it does not contain an organic siloxane structure, its resistance to ethylene glycol is relatively poor. After aging, the cured product swells and dissolves, and the ethylene glycol aqueous solution is slightly turbid.
[0052] The formula of Comparative Example 3 contains low-Tg difunctional acrylate, and the resulting cured product has a relatively low Tg, poor heat resistance, and relatively poor ethylene glycol resistance. After aging, the cured product swells and dissolves, and the ethylene glycol aqueous solution is also very turbid.
Claims
1. A micropore plugging agent for flexible graphite bipolar plates of fuel cells, characterized in that: include: 30-50 parts by weight of an organosilicon double-capping agent with two (meth)acryloyloxy groups at both ends and 50-70 parts by weight of a high Tg methacrylate monomer, the total of which is 100 parts by weight, as well as 0.5-2 parts by weight of a leveling agent and 0.2-1.0 parts by weight of a free radical thermal initiator; The organosilicon double-capping agent with two (meth)acryloyloxy groups at both ends has the following structure: Wherein, R1 represents a methyl group or a hydrogen atom.
2. The plugging agent according to claim 1, characterized in that: The organosilicon double capping agent with two (meth)acryloyloxy groups at both ends is prepared by the following steps: The first step is to use a hydrogen-containing double-capped compound and trimethylolpropane monoallyl ether to carry out a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capped compound containing two hydroxyl groups at both ends. Step 2: The double-capped compound containing two hydroxyl groups at both ends and an excess of (meth) acrylic acid are subjected to an esterification and dehydration reaction in the presence of an acidic catalyst and a cyclohexane water-carrying agent to generate a double-capped compound with two (meth) acryloyloxy structures at both ends: Wherein, R1 represents a methyl group or a hydrogen atom.
3. The plugging agent according to claim 2, characterized in that: A free radical inhibitor is added in the esterification dehydration reaction, and the amount of the free radical inhibitor added is 0.01% to 1% of the total mass of the reactants.
4. The plugging agent according to claim 3, characterized in that: The free radical inhibitor is any one or more of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone and 2,6-di-tert-butyl-4-methylphenol.
5. The plugging agent according to claim 2, characterized in that: The acidic catalyst for the esterification dehydration reaction is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, and the added amount is 0.1% to 5.0% of the total mass of the reactants.
6. The plugging agent according to claim 1, characterized in that: The high Tg methacrylate monomer is selected from any one of isobornyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuran methacrylate, tricyclodecyl (meth)acrylate, dicyclopentadiene (meth)acrylate, (meth)acryloylmorpholine and N,N-dimethylacrylamide, preferably isobornyl (meth)acrylate, dicyclopentadiene (meth)acrylate or tricyclodecyl methacrylate.
7. The plugging agent according to claim 1, characterized in that: The leveling agent is selected from any one of German BYK leveling agents BYK-333 and BYK-3505, and three positive polymer superdispersants CH-1, CH-2, CH-3, CH-5, CH-6, CH-7, CH-8, and CH-9.
8. The plugging agent according to claim 1, characterized in that: The free radical thermal initiator is an azo or peroxide free radical thermal initiator with a decomposition temperature of 80-95° C., preferably any one of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
9. The plugging agent according to claim 1, characterized in that: The plugging agent also includes any one or more of an antioxidant, an anti-aging agent or a fluorescent agent.
Citation Information
Patent Citations
A microporous filler for a bipolar graphite plate for a hydrogen fuel cell
CN107706430B
Proton conductive film, membrane-electrode assembly, and solid polymer electrolyte fuel cell
CN101622745A
Silicon compound, coating agent resin composition, molded body, and image display device
CN106164080A
UV (ultraviolet) adhesive for difficult-to-adhere materials
CN119081641A